The Factor V Leiden Mutation which Predisposes to Thrombosis Is Not Common in Patients with Antiphospholipid Syndrome - Dizon-Townson, Donna; Hutchison, Christopher; Silver, Robert; Branch, D Ware; Ward, Kenneth (Thrombosis and Haemostasis, 1995)
Antiphospholipid syndrome is associated with venous, arterial, and placental thrombosis, possibly through autoantibody impairment of phospholipid-dependent protein C activation. Recently, a missense mutation in the factor V gene (1691 G → A) has been identified that results in an abnormal factor V product (1). This mutation, known as the Leiden mutation, causes an amino acid substitution of glutamine for arginine at position 506 in the factor V molecule and renders the protein resistant to proteolytic inactivation by activated protein C and thus predisposes to thrombosis (2, 3). We hypothesized that some individuals with antiphospholipid syndrome may also carry the Leiden mutation, and thus have a “second hit” predisposition to thrombosis. To test this hypothesis, allele-specific hybridization and allele-specific restriction analysis were used to test for the Leiden mutation in thirty women with the antiphospholipid syndrome, 10 of whom had a history of thrombosis. None of the women were heterozygous or homozygous for the factor V mutation. We conclude that the presence of the factor V Leiden mutation is not a prerequisite for the thrombotic events in patients with antiphospholipid syndrome, due to the occurrence of thrombosis seen in patients lacking the factor V mutation.